A SENSE OF DIRECTION: BRAIN STIMULATION IN LATERALISED BRAIN FUNCTION. Issue 11 (14th October 2015) - Li, Lucia; Leech, Robert; Seemungal, Barry; Malhotra, Paresh; Sharp, David
Abstract : Many cognitive functions demonstrate varying degrees of hemispheric lateralisation. Lateralised pathology can lead to striking deficits, such as the dyscalculia produced by dominant parietal lesions. Transcranial direct current stimulation (tDCS) non-invasively delivers weak electrical currents to the brain, resulting in transient changes in neuronal excitability: anodal tDCS is thought to be facilitatory, whilst cathodal is inhibitory. We investigated the effect of bi-parietal tDCS on numeracy, spatial attention and, sustained attention. We hypothesised that tDCS has distinct effects because of varying lateralisation (numeracy left, spatial attention right and sustained attention uncertain). We performed a single-blinded, cross-over, sham-controlled study. Eighteen healthy right-handed subjects performed cognitive tasks during 3 sessions of bi-parietal tDCS stimulation: sham, right cathodal plus left anodal (RC/LA) and left cathodal plus right anodal (LC/RA). Inhibition of the left parietal lobe by LC/RA stimulation impaired numeracy performance, compared to sham or RA/LC stimulation (F(2, 16)=3.684, p=0.048). LC/RA stimulation also resulted in significantly impaired sustained attention performance, as compared to sham or RA/LC stimulation (F(2, 34)=5.3, p=0.01). We demonstrate that bilateral tDCS modulates numeracy and sustained attention in an electrode polarity-dependent manner. This method can be used to interrogate lateralised cognitive functions in future studies of healthy and diseased populations.